2017
DOI: 10.19080/gjo.2017.04.555640
|View full text |Cite
|
Sign up to set email alerts
|

Types of Foreign Body In Ear, Nose And Throat In Western Part of Nepal

Abstract: Introduction: Foreign body in ear, nose and throat though being a common entity needs specific technique and condition to remove.Methods: A retrospective descriptive study was done in patients presenting in a tertiary referral center. Demography along with site, type of foreign body along with its removal was recorded in a proforma.Results: Out of total 211 cases recorded, 118 were male and 93 female. Most of them were less than five years. Most of the presentation was in nose (40.2%) followed by ear (34.1%) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 10 publications
2
6
0
Order By: Relevance
“…In this study, common nasal FB included beads, stones and beans.The FB observed in the nose in our study were found mainly in children under 14 years of age (82.33%). These findings are consistent with the literature (2,9,13,14,16) . Contrary to FB in the ear, men (867 cases -58.6%) had a higher incidence than women (632 cases -41.4%).These results are in contrast with the study of El-Taher (5) .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…In this study, common nasal FB included beads, stones and beans.The FB observed in the nose in our study were found mainly in children under 14 years of age (82.33%). These findings are consistent with the literature (2,9,13,14,16) . Contrary to FB in the ear, men (867 cases -58.6%) had a higher incidence than women (632 cases -41.4%).These results are in contrast with the study of El-Taher (5) .…”
Section: Discussionsupporting
confidence: 94%
“…The most common foreign bodies taken out were plant seed (41.6%), plastic parts (20.8%), and insects (13.8%). Most foreign bodies entered the throat included coins (58.8%) and bones (39.2%) (16). In our study, Swallowed FBs were the most common (50%), followed by nasal FBs (35%) and, finally, ear FBs (15%).…”
Section: Discussionmentioning
confidence: 51%
“…This is in accordance with the results of research conducted by Bhatta in 2017 which said that foreign bodies were most commonly found in the nose. 11 In contrast to research conducted by Taiwo in 2017 which stated that foreign bodies were most commonly found in the ears. 12 Children often insert a foreign object into the nose, because the nose is the organ in the body part that is most easily accessible and the discovery of foreign objects is often in accordance with the use of the dominant hand.…”
Section: Discussionmentioning
confidence: 87%
“…Foreign body is a common ENT emergency accounting for about 11% of the cases in ENT emergency. 5 As reported by Bhatta R, et al 6 digestive tract is the commonest site for foreign body impaction after ear, nose and respiratory tract.…”
Section: Discussionmentioning
confidence: 91%